Comparative analysis on the usage of Ilocano dialect among the Ilokanos and Tabukenos in Tabuk City - Reyes, Paulino P. II (2019)
This study aims to compare the usage of Ilocano dialect among the Ilocanos and Tabukenos in Tabuk City, particularly on the prefixes, root words, and basic sentence constructions. The study sought answers on the following objectives: to compare the usage of Ilocano dialect among the Ilokanos and Tabukenos in Tabuk City in terms of what prefixes are commonly used, tenses of verbs, and basic sentence construction, to translate the standard terms (English terms) by both the Ilokanos and the Tabukenos and to determine the following differences and similarities: Root word, Commonly used expressions, Numbers, Body parts, Members of the family and Sentences. Using the qualitative comparative analysis of research since it gathered data through interviews using the guide questions and prepared selections for translation, this study was conducted in Tabuk City, particularly in barangay Tuga where the Ilokano group originally settled and some urban barangays of Tabuk City. The informants were 15 Genuine Ilocanos and 15 Tabukenos taken through the fishbowl method. Pronunciation was the determinant in the analysis of the data. Based on the translations made by the respondents, there are words or terminologies that are commonly used, and there are different translations also; however, they have the same meaning. Regarding the tenses of verbs, each tense has its structure similar to the Filipino language structure. The following are recommended: maintain the structure of the Ilokano language sentences and other translations, teachers who are handling this subject (Ilokano) should emphasize the correct structure of sentences and translation of every expression, time, body part, and the like to preserve its originality and uniqueness.
Keywords: Ilokano dialect; Language and languages